2020
DOI: 10.46266/njes.1003
|View full text |Cite
|
Sign up to set email alerts
|

Public knowledge and acceptance of genetically modified organisms in Shiraz, Iran

Abstract: The application of new technologies, such as biotechnology, has its proponents and opponents. Public acceptance is an essential factor to develop biotechnology as a modern technology. The present study was conducted to assess the level of public perception and attitude toward the risks and advantages of genetically modified organisms (GMOs) in Shiraz, Iran. A questionnaire survey was conducted among people between the ages of 15 and 65 years old, with an average age of 33 years old. This study revealed that va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…Furthermore, participants who had attained tertiary level of education were three times more likely to accept GMFs compared to those who had never attained education or those that had less levels. A study by Abedi has indicated that education has a great influence on public attitude towards genetically modified organisms(32). Therefore, the higher the level of education, the more the likelihood to accept to GMFs uptake or adoption.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, participants who had attained tertiary level of education were three times more likely to accept GMFs compared to those who had never attained education or those that had less levels. A study by Abedi has indicated that education has a great influence on public attitude towards genetically modified organisms(32). Therefore, the higher the level of education, the more the likelihood to accept to GMFs uptake or adoption.…”
Section: Discussionmentioning
confidence: 99%